Entropy Solution to Nonlinear Elliptic Problem with Non-local Boundary Conditions and L¹-data (Journal of Partial Differential Equations, 2017)
"We study a nonlinear elliptic problem with non-local boundary conditions and L\u00b9-data. We prove an existence and uniqueness result of an entropy solution."
Keywords: Entropy solution; non-local boundary conditions; Leray-Lions operator